Analisis Proses Morfologis Afiksasi pada Teks Deskriptif Peserta Didik Kelas VII - Muhamad Ichsan Nurjaman; Tri Mahajani; Sandi Budiana (FKIP UNIVERSITAS PAKUAN, 2015)
The research focus was the morphological process of affixation which were correct and incorrect in descriptive texts. It was conducted to the students of SMPN 1 Leuwiliang grade VII, in the district of Bogor. The method employed was qualitative descriptive. The data was taken from descriptive texts written by the students of grade VII at SMPN 1 Leuwiliang, in the district of Bogor. The result shows that there were 93 data from 31 descriptive texts. From the 93 data there were 142 affixed words, such as ber-, meN-, peN-, di-, –an, and –kan. Based on the analysis, the affixes that were correct according to morphological process were 115 words and those which were incorrect were 27 words. The correct affixed words were ber- as many as 22 words (19,13%), words with affix meN- were 41 words (35,65%), affix peN- were 8 words (6,95%), affix di- were 21 words (18,26%), affix –an were 14 words (12,17%), and affix –kan were 9 words (7,82%). The words containing incorrect affixes were words with the affix of ber- as many as 2 words (7,40%), affix meN- were 6 words (22,22%), affix peN- were 3 words (11,11%), affix di- were 12 words (44,44%), affix –an was 1 word (3,70%), and affix –kan were 3 words (11,11%). Therefore, the affixation in morphological process in the descriptive texts written by the students of grade VII at SMPN 1 Leuwiliang, in the district of Bogor, contained affixes and the most frequently and correctly used was the affix of meN- which were as many as 41 words (35,65%). The affix that was frequently used but incorrectly was the affix of di- which were as many as 12 words (44,44%).